The Effects of Liberalizing Migration on Permanent Migrants' Education Structure. (14th November 2013) - Huber, Peter; Bock‐Schappelwein, Julia
Abstract: This article explores how the full liberalization of migration as a consequence of Austria's European economic area (EEA) accession in 1994 impacted on the education structure of migrants to Austria. To identify the effects of this policy change, use is made of the fact that only migrants from EEA member states were affected, while third country citizens were not. Robust evidence is found that the share of low educated permanent migrants from the EEA to Austria reduced relative to the share of low educated permanent migrants from other countries after Austria's EEA accession. This suggests that liberalizing migration may be an effective way to improve the skill structure of migrants in countries with a high share of low‐skilled migrants.